2015
DOI: 10.1186/s12884-015-0580-6
|View full text |Cite|
|
Sign up to set email alerts
|

Pregnancy complications and birth outcomes among women experiencing nausea only or nausea and vomiting during pregnancy in the Norwegian Mother and Child Cohort Study

Abstract: BackgroundTo compare pregnancy complications and birth outcomes for women experiencing nausea and vomiting in pregnancy, or nausea only, with symptom-free women.MethodsPregnancies from the Norwegian Mother and Child Cohort Study (n = 51 675), a population-based prospective cohort study, were examined. Data on nausea and/or vomiting during gestation and birth outcomes were collected from three questionnaires answered between gestation weeks 15 and 30, and linked with data from the Medical Birth Registry of Norw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(106 citation statements)
references
References 56 publications
(103 reference statements)
5
92
4
1
Order By: Relevance
“…In the present study, female sex of the offspring was not associated with NVP, contrasting with what can be found in the literature [19]. One study found that women with NVP are more likely to develop pregnancy complications (proteinuria, high blood pressure, or pre‐eclampsia) than women without NVP [20]. Therefore, it is important to identify high‐risk patients with NVP and objectively evaluate their symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, female sex of the offspring was not associated with NVP, contrasting with what can be found in the literature [19]. One study found that women with NVP are more likely to develop pregnancy complications (proteinuria, high blood pressure, or pre‐eclampsia) than women without NVP [20]. Therefore, it is important to identify high‐risk patients with NVP and objectively evaluate their symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…Women with NVP have significantly increased odds for high blood pressure and preeclampsia compared with symptom-free pregnant women (Chortatos et al, 2015). In addition, in 10–35% of patients the symptoms of NVP lead to increased feelings of depression, and may cause a negative impact on employment, household duties, parenting and family relationships (Attard et al, 2002; Mazzotta et al, 2000b; Mazzotta et al, 2000c; Niebyl, 2010; O’Brien et al, 1992; Smith et al, 2000).…”
Section: Nausea and Vomiting Of Pregnancymentioning
confidence: 99%
“…In contrast to the burden that NVP can be for the pregnant woman, most studies have found that mild NVP is associated with favorable outcomes for the fetus including reduced odds for low birth weight and small for gestational age (Brandes, 1967; Chortatos et al, 2015; Little, 1980; Medalie, 1957; Milkovich et al, 1976; Petitti, 1986; Tierson et al, 1986), reduced risk of preterm delivery (Brandes, 1967; Jarnfelt-Samsioe, 1987; Klebanoff et al, 1985; Koren et al, 2014; Medalie, 1957; Milkovich et al, 1976; Petitti, 1986; Tierson et al, 1986) and reductions in the likelihood of miscarriage (Jarnfelt-Samsioe, 1987; Klebanoff et al, 1985; Koren et al, 2014; Medalie, 1957; Milkovich et al, 1976; Petitti, 1986; Weigel et al, 1989). …”
Section: Nausea and Vomiting Of Pregnancymentioning
confidence: 99%
“…(2015) tarafından yapılan gebelik döneminde bulantı kusması olan kadınlarla, olmayan kadınları karşılaştıran bir çalışmada (n= 51.675) gebelik komplikasyonları ve doğum sonuçları yönünden iki gurup kıyaslanmış ve gebelikte bulantı kusmanın gebelik komplikasyonlarıyla bağlantılı olduğu ancak doğum sonuçla-rıyla bağlantılı olmadığı saptanmıştır. 26 DSÖ (2016), yapılan meta analiz çalışmaları-nın sonuçlarına göre; zayıf kalitede kanıt düze-yinde zencefil, papatya ve akupunkturu, orta kalitede kanıt düzeyinde ise B6 vitaminini gebelikte bulantı kusmanın azaltılmasında tavsiye ettiğini belirtmektedir. Üç büyük öğün yemek yerine küçük porsiyonlarda az ve sık yemek ve az yağlı ve sindirimi kolay gıdalar (muz, pirinç, elmalı çay, tost ve çay) yemek gerektiği, Zencefil, zencefil çayı, zencefil kapsülleri ve zencefilli şekerlerle yapılan içecekleri tüketmenin gebeye iyi geleceğini ve şiddetli kusan gebelerde mide özsuyunun diş minesine zarar vermesini engellemek için, bir çay kaşığı karbonatla gargara yapılmasını, böylece ağız içi asidin nötralize edilebileceğini belirtmiştir.…”
Section: Bulanti-kusmaunclassified